A nanoparticulate system that enhances the efficacy of the tumoricide Dz13 when administered proximal to the lesion site - Tan, M.; Dunstan, D.; Friedhuber, A.; Choong, P.; Dass, Crispin (Elsevier, 2010)
We demonstrate that Dz13, a DNA enzyme that cleaves c-Jun mRNA, and is capable of inhibiting cancer cell growth in vitro, can be encapsulated into chitosan nanoparticles. For optimisation of this chitosan-based formulation, pH 6, 0.02% chitosan concentration, and 55 °C were found to be best among the variables tested. Particles were 50-300. nm in diameter and encapsulated Dz13 was active when particles were exposed to cancer cells. Nanoparticles were stable during storage even for a month, but were not stable in mouse and human serum. In two different clinically-relevant disease models, and using a clinically-adoptable dosing regimen, these Dz13-nanoparticles were shown to be efficacious against a bone tumour (osteosarcoma), for which no real cure exists currently. However, no toxicity against other bone-dwelling cells was observed with the formulation, and no side-effects were noted in vivo in lymphatic and reticuloendothelial tissues proximal and distal to the administration site.